Knowledge on Prevention of Mother to Child Transmission of HIV among Pregnant Women of Damak - Subedi, Sabitra; Mandal, Punam Kumari; Choudhary, Archana (Bouddhik Abhiyan (बौद्धिक अभियान), 2023)
The goal of the global intervention is to stop the spread of HIV from an HIV-positive mother to her unborn child during pregnancy, birth, or breastfeeding. A significant issue with world health is HIV. In comparison to other age groups, the prevalence of HIV is highest among those who are in reproductive age groups globally. The main method of HIV transmission among children is now mother-to-child transmission.. The main objective of the study is to assess the level of Knowledge on the Prevention of Mother-Child Transmission among Pregnant Women at Damak Hospital. This descriptive cross-sectional study was carried out in the ANC clinic of Damak Hospital from June 2 to June 15 in 2019. A complete enumerative sampling technique was used. The total sample size was 80. All the required information was collected through the interview schedule. The interview was taken by an investigator oneself in a face-to-face interview with the pregnant woman. Among 80 respondents, the mean age of the respondent was 25.84 years of which 42.5% were Primigravida and 57.5% of the respondents were Multigravida. Similarly, 37.5% of respondents had higher education and above. Most (76.3%) of respondents mentioned books as the major source of information. Among the studied respondent, 8.8% of the respondents have good knowledge, 58.8% have moderate knowledge and 32.4% have poor knowledge of PMTCT. The level of knowledge was statistically associated with occupation (p=0.04) whereas the level of knowledge was not associated with other socio-demographic variables: age groups, gravida. In this study, respondents have a moderate level of knowledge on the prevention of mother-to-child transmission and the level of knowledge was statistically associated with the occupation of respondents.